The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1370/afm.1089
|View full text |Cite|
|
Sign up to set email alerts
|

Primary Care Practice Development: A Relationship-Centered Approach

Abstract: PURPOSE Numerous primary care practice development efforts, many related to the patient-centered medical home (PCMH), are emerging across the United States with few guides available to inform them. This article presents a relationship-centered practice development approach to understand practice and to aid in fostering practice development to advance key attributes of primary care that include access to fi rst-contact care, comprehensive care, coordination of care, and a personal relationship over time. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
217
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(226 citation statements)
references
References 65 publications
(74 reference statements)
5
217
0
4
Order By: Relevance
“…39,40 Most of the barriers and facilitators identified relate directly to relationship building. For example, the barriers of insufficient technology or physician and patient resistance limit care coordinators' ability to cultivate the necessary relationships for effective communication.…”
Section: Study Contributionmentioning
confidence: 99%
“…39,40 Most of the barriers and facilitators identified relate directly to relationship building. For example, the barriers of insufficient technology or physician and patient resistance limit care coordinators' ability to cultivate the necessary relationships for effective communication.…”
Section: Study Contributionmentioning
confidence: 99%
“…24,49,52,78,79 This study' s strengths include our randomized design using a control group with a lagged intervention, multimethod comparative case study process assessment, research team with previous facilitation experience, number and diversity of practices, simultaneous inclusion of 3 unrelated outcomes, strong longitudinal practice relationships, and large improvements in all outcomes across all practices. 43 Facilitation responsibilities were handled separately from research data collection, supporting the potential for dissemination beyond the research setting.…”
Section: Figurementioning
confidence: 99%
“…In particular, clinicians confirmed that sharing performance data, a key element of the LLC design, was critical to the effectiveness of the intervention and confirmed the importance of social relations and trust in establishing a productive learning environment. 31,32 Not surprisingly, travel was a barrier to LLC attendance, even when meetings were scheduled at lunch time, and meetings held either by video or telephone were perceived as less effective unless groups were known to each other.…”
Section: Discussionmentioning
confidence: 99%